A Systematic Review of Sustainable Fresh Fruit and Vegetable Supply Chains - ÇOBANOĞLU, EMİNE; VAYVAY, ÖZALP (MDPI, 2022)
Fresh fruit and vegetables are crucial for human health. Their fibrous structure and high nutritional value are essential for people’s well-being. This study aims to provide a review of the current state of knowledge and practices regarding fresh fruit and vegetable supply chains (FFVSC). The reviewed papers are divided into categories according to their findings, research purposes, tools and messages used. Our objective is to guide both academics and practitioners by pointing out significant streams of research with respect to these categories. For a better understanding, these sub-groups are essentially based on their common research purpose, and the tools and methods they adopted are explained. Therefore, this study sheds light on research related to FFVSCs for those who are new to this area or planning to conduct in-depth research on directions suggested by studies in this area. The related literature was classified into eight categories: namely, (1) value chain indicators of FFVSCs, (2) food-related problems/postharvest losses along FFVSCs, (3) roles of parties involved in the FFV value chain, (4) review papers, (5) technological trends in FFVSCs, (6) packaging issues of FFVSCs, (7) logistics solutions of FFVSCs, and (8) sustainable FFVSCs. Details on the tools and methods employed in these studies are summarized in Appendix B. To the best of the authors’ knowledge, the related literature lacks a comprehensive review that investigates different aspects of FFVVCs in detail. Thus, this study contributes towards a better understanding of the related literature and can be used as a guide for future studies. © 2022 by the authors. Licensee MDPI, Basel, Switzerland.
Keywords: Fresh fruits and vegetables; Perishable food; Supply chain; Value chain